Mapping an avirulence gene in the sunflower parasitic weed Orobanche cumana and characterization of host selection based on virulence alleles - Álvaro Calderón-González; Belén Fernández-Melero; Lidia del Moral; Stéphane Muños; Leonardo Velasco; Begoña Pérez-Vich (BMC Plant Biology, 2024)
Abstract Background Sunflower broomrape (Orobanche cumana Wallr.) is a holoparasitic plant that jeopardizes sunflower production in most areas of Europe and Asia. Recently, populations with increased virulence, classified as race GGV, have been identified in Southern Spain’s Guadalquivir Valley gene pool. These populations overcome resistance genes in hybrids resistant to the predominant race FGV. This study aimed to (i) determine the inheritance and map the avirulence trait segregating in a cross between O. cumana individuals from populations EK23 (FGV) and IN201 (GGV), and (ii) characterize the host effect on the IN201 parental population allelic diversity. Results A segregating population consisting of 144 F2:3 families was evaluated for virulence using a differential sunflower genotype (Hybrid 1, resistant to race FGV and susceptible to race GGV) and genotyped with SNP markers. The ratio of avirulent to virulent F2:3 families was not significantly different to 1:3 (χ2 = 0.93; P = 0.34), indicating monogenic control of the avirulence/virulence trait. The Avr G−GV locus was mapped on the upper end of O. cumana chromosome 2, 9.2 cM distal from the SNP markers OS04791 and OS02805. Secretome analysis in the Avr G−GV region revealed a cysteine-rich CAP superfamily- and a glucan 1,3-beta-glucosidase family 3-encoding genes as possible candidates for Avr G−GV . SNP allelic analysis on the IN201 population parasitizing a highly susceptible genotype or the differential genotype Hybrid 1 showed that (i) IN201 structure was shaped towards virulent alleles at SNP loci linked to Avr G−GV (ii) there were significant allelic frequency differences associated with the host genotype at Avr G−GV –linked loci. Conclusions This study mapped for the first time an avirulence gene in parasitic plants using a classical genetic approach, confirmed a gene-for-gene model in the O.cumana –sunflower system, and showed the implication of this single avirulence gene in determining the structure of broomrape populations subjected to selection pressure posed by a resistant genotype. The results will contribute to a better understanding of the interaction between crops and weedy parasitic plants, and to effectively manage evolution of virulence by sustainable control strategies based on host genetic resistance.